The Effect of Work Life Balance on Organizational Commitment with Job Satisfaction as a Mediating Variable among Nurses at Rumah Sakit Tentara dr. Reksodiwiryo - Waruwu, Eka Maria Putri; Sarianti, Rini (Human Resource Management Studies, 2025)
In organizational behavior, organizational commitment is crucial. Every person who is dedicated to themselves wants to keep helping the company succeed. According to this study, the primary elements that boost an individual's commitment to their company are work-life balance and job satisfaction. ThusThe goal of this research is to ascertain how work-life balance and organizational commitment are mediated by job satisfaction. The objects in this study were 113 nurses from dr. Reksodiwiryo Military Hospital, who were selected based on cluster proportional random sampling technique and using questionnaire to gather data. This research employed a quantitative methodology and version 4.1.1.2 of SMARTPLS was used to evaluate the data. The findings show that job satisfaction drives organizational commitment, Organizational commitment is influenced by work-life balance, and the connection among work-life balance and organizational commitment can be mediated by job satisfaction.